REPRESENTATION OF EVFEMIZMS IN PUBLIC DISCOURSE - Kabilova Sayyora Abdukarimovna (Scholar Express Journal, 2024)
The main categories forming the text are: time, space, and personal categories. In this part of our research, the unexplored functions of euphemisms in the journalistic text are analyzed are marked as participation.
Keywords: phenomenon; complex syntactic; syntactic connections